A beam or a slab? Classification of structural members according to the theory of solid mechanics and engineering literature - Samborski, Marcin; Słowik, Marta (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
The basic solid mechanics definition of a bar-type member and a shell-type member gives rules for the classification of structural reinforced concrete members on beams and slabs. But the definition of a beam and a slab, which we can find in an engineering literature, are not precise and this fact can lead to the incorrect determining of stress distribution in reinforced concrete members.